(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
This paper combines literature on Circular Economy, Business Innovation and Product Service System Design (PSSD) to outline different opportunities on the application of PSSD in the process of transition to a new economic model. Moving to a closed-loop industrial model would naturally introduce new opportunities for development of PSS because of the essential principles of the Circular Economy. These would include the ideas of delivering capability rather than ownership, extending product value (remanufacturing), shared ownership, reverse logistics etc. Value for the user and the environment is found in product but mainly in service content and serves as an example for the positive effect PSSs can have in the process of transition to a circular economy model. The argument is supported with case studies that serve to illustrate the potential success of circular services and systems.